2020
DOI: 10.1186/s11658-020-00213-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Downregulation of miR-483-5p decreases hypoxia-induced injury in human cardiomyocytes by targeting MAPK3

Abstract: Background: MiR-483-5p was recently identified as a risk factor in the early stages of acute myocardial infarction (AMI) patients. Here, we further investigated how miR-483-5p affects cardiomyocyte apoptosis and oxidative stress under hypoxic conditions. Methods: Plasma samples were collected from AMI patients and healthy volunteers. The expression of miR-483-5p was determined using quantitative real-time PCR. An in vitro hypoxic model was constructed to mimic AMI in AC16 cells. Cell viability, apoptosis and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Within the realm of cardiovascular disease, we found differential expression of miR-484, miR-433, miR-320 and miR-383-5p, all of which have previously been documented to play an important role in the heart's response to ischemia/reperfusion injury [40][41][42][43]. Additionally, miR-484-5p and miR-484-3p are suggested as potential therapeutic targets to limit hypoxia-induced myocardial injury [44,45]. Other differentially expressed miRNAs are also associated with cardiac disease; miR-134 is elevated in early stages of myocardial infarction and its inhibition can decrease apoptosis of cardiomyocytes [46,47].…”
Section: Principal Resultsmentioning
confidence: 69%
“…Within the realm of cardiovascular disease, we found differential expression of miR-484, miR-433, miR-320 and miR-383-5p, all of which have previously been documented to play an important role in the heart's response to ischemia/reperfusion injury [40][41][42][43]. Additionally, miR-484-5p and miR-484-3p are suggested as potential therapeutic targets to limit hypoxia-induced myocardial injury [44,45]. Other differentially expressed miRNAs are also associated with cardiac disease; miR-134 is elevated in early stages of myocardial infarction and its inhibition can decrease apoptosis of cardiomyocytes [46,47].…”
Section: Principal Resultsmentioning
confidence: 69%
“…The MAPK signaling pathway is closely related to cell injury [ 53 ]. For example, MAPK3, also known as extracellular-regulated protein kinase 1 (ERK1), is reported to downregulate the expression of miR-483-5p post-transcriptionally, leading to apoptosis and oxidative stress in human cardiomyocytes under hypoxia [ 54 ]. Another study reported that inhibiting miR-124 can cause the overexpression of MAPK14, which, in turn, activates the MAPK signaling pathway and promotes lung cell apoptosis and inflammation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of myocardial infarction in patients with type I diabetes may be related to mitochondrial dysfunction, so erbB2 is also a highly correlated gene [32] . The MAPK3 pathway is involved in the repair of myocardial ischemia [33,34,35] . This may be related to the body's self-repair after acute myocardial infarction, which may provide a target for future treatment.…”
Section: Discussionmentioning
confidence: 99%